2021
DOI: 10.1016/j.xnsj.2021.100053
|View full text |Cite
|
Sign up to set email alerts
|

Prone-transpsoas as single-position, circumferential access to the lumbar spine: A brief survey of index cases

Abstract: Background case description Prone transposoas (PTP) is a novel approach to the lateral lumbar interbody fusion that harnesses the advantages of minimally invasive surgery with circumferential access to the lumbar spine in a single position. We present the peri-operative course of four index cases of patients having undergone PTP at a single institution. Outcome Pre and post-operative spinal imaging with alignment parameters, operative approach, and patient outcome are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In this study, we found a mean operative duration of 226.2 minutes, which is even less than that reported by Soliman et al 15 The EBL in this study was 138.4 mL, which is within the range of blood loss for the standard LLIF reported in the literature (19-240 mL). 12,[23][24][25][26] In this study, a single case of vascular injury occurred during the ALIF procedure at the adjacent level and was not attributed to the PTP procedure. Aguirre et al 27 conducted a systematic review of vascular injury rates after standard LLIF, finding that it ranged between 0% and 2.6%.…”
Section: Length Of Stay and Intraoperative Datamentioning
confidence: 70%
“…In this study, we found a mean operative duration of 226.2 minutes, which is even less than that reported by Soliman et al 15 The EBL in this study was 138.4 mL, which is within the range of blood loss for the standard LLIF reported in the literature (19-240 mL). 12,[23][24][25][26] In this study, a single case of vascular injury occurred during the ALIF procedure at the adjacent level and was not attributed to the PTP procedure. Aguirre et al 27 conducted a systematic review of vascular injury rates after standard LLIF, finding that it ranged between 0% and 2.6%.…”
Section: Length Of Stay and Intraoperative Datamentioning
confidence: 70%
“…Single-position lateral fusion approaches in the lateral decubitus position have been performed and studied, with some reports documenting a nearly 1-hour decrease in the mean operative time compared with two-stage procedures without compromising spinopelvic parameters. [10][11][12] However, this approach is associated with a higher rate of facet joint violation, leading to unnecessary repeat reoperation. 13 The PTP technique addresses certain drawbacks associated with both staged and lateral decubitus LLIF techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This falls within the range of 19 to 240 mL of blood loss for these procedures reported in the literature. 9,[22][23][24]26…”
Section: Blood Lossmentioning
confidence: 99%